DESIGN AND CONSTRUCTION OF AUTOMATIC PORTABLE DISINFECTANT BUTTON TO PREVENT THE SPREAD OF THE COVID-19 VIRUS - Sujiwa, Akbar; Raharjo, Irwan Puji (BEST, 2021)
The Covid-19 virus is currently rampant in the world, especially in Indonesia, the spread of the Covid-19 virus is getting faster and wider. Even the spike in cases was unpredictable. Since entering Indonesia last March. In an effort to prevent it, almost every area carries out a body temperature test and sprays disinfectants on people who enter the area. This study aims to produce an automatic disinfectant sprayer and test its effectiveness. The method used is the data collection analysis method by testing the product. This tool uses ultrasonic sensors as object detectors, MLX 90614 sensors as temperature readers and Arduino Uno R3 as controllers. The output uses a Relay module that is connected to a Water Pump that sprays disinfectant liquid through a spray mist. This tool is effective in its manufacture and is able to detect objects in the area of ​​​​the disinfectant booth. The results of the study found that the level of accuracy of the MLX 90614 sensor which was calibrated with the Thermogan measuring instrument had an accuracy of reading the temperature of 98.8% with a difference of 1.16%.